Photolytic and Catalytic Destruction of Organic Waste Water Pollutants; IOP Conference Series: Earth and Environmental Science; Vol. 50 : Ecology and safety in the technosphere: current problems and solutions - Torosyan V. F. Vera Fedorovna; Torosyan E. S. Elena Samvelovna; Kryuchkova S. O.; Gromov V. E. (2017, 2017)
Title screen